Structural and functional properties of neocartilage construct engineered in poly (Lactic-co-Glycolic Acid) (PLGA) based scaffolds - Md Ali @ Tahir, Aisyah Hanani; Mohamed Amin, Muhammad Azri Ifwat; Noor Azmi, Azran Azhim; Sha'ban, Munirah (UTHM Press, 2019)
The study aims to assess the structural and functional properties of in vitro three-dimensional (3D) PLGA-based hybrid scaffolds seeded with chondrocytes, particularly in terms of the production of specific cartilaginous extracellular matrix (ECM). The PLGA scaffolds were incorporated with atelocollagen and/or fresh fibrin and assigned to four groups; PLGA only as control, PLGA-fibrin (PF), PLGA-atelocollagen (PA) and PLGA-atelocollagen-fibrin (PAF). The resulting PLGA hybrid scaffolds were characterized based on gross appearance, attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy analysis, porosity and swelling tests as well as cytocompatibility analysis using cell proliferation (MTT) assay. All scaffolds seeded with cells were cultured for three weeks in vitro. Macroscopic changes were recorded using photographs. Microscopic evaluation of ‘cells-scaffolds’ construct was done using Haematoxylin and Eosin (H&E), Safranin O, Alcian Blue, Toluidine Blue and scanning electron microscopy (SEM). The production of cartilage specific ECM was measured using sulphated glycosaminoglycan (sGAG) assay. Based on physical characterizations, PLGAbased hybrid scaffolds have been successfully manufactured and showed no cytocompatibility issues. The PAF exhibited cartilaginous tissue morphology better than other scaffold groups, grossly and microscopically. On SEM, the presence of branching fibers that produce a web-like network on the surface of PLGA-based hybrid scaffolds indicated ECM secretion. This is supported by the manifestation of glycosaminoglycan and as well as proteoglycan through histology and sGAG assay. This present study indicated that PLGA-based hybrid scaffolds promote formation of neocartilage in vitro.